AB1114 CALPROTECTIN IN SERUM AND SYNOVIAL FLUID AS A BIOMARKER IN ACUTE ARTHRITIS. (June 2019) - Aguilar-Zamora, Marta; Montolio-Chiva, L; Morena, Isabel de la; López Ortega, José María; Olmos, Carlos Feced; Orenes Vera, Ana V.; Vázquez-Gómez, I; Valls-Pascual, Elia; Ybáñez-García, D; Martínez-Ferrer, à; Sendra-García, A; Torner-Hernández, I; et al.
Abstract : Background: There are increasingly data about the usefulness of calprotectin levels in chronic inflammatory arthritis and its relationship with prognostic factors. However, few data are available on its role in the diagnosis of acute arthritis. Objectives: To evaluate the possible usefulness of testing plasma and synovial fluid (SF) calprotectin levels as a predictor of the final diagnosis behind an acute mono or oligoarthritis. Methods: Longitudinal observational study. We included non-consecutive patients referred to the rheumatology emergency department with suspected mono or acute oligoarthritis for a period of 23 months. Patients with a previous diagnosis of inflammatory, infectious or neoplastic disease were excluded. All of them underwent diagnostic arthrocentesis and blood extraction simultaneously. The SF was evaluated under optical microscopy immediately for the study of microcrystals. Samples of SF were also routinely sent to microbiological culture, and calprotectin levels (SFC) and cell count were determined. In blood, the calprotectin level (SC), CRP and ESR were determined. The calprotectin level in plasma was determined by an automated fluoroenzyme-immunoassay technique on an ImmunoCAP250 analyzer (Thermo Fisher). All patients were followed until diagnostic confirmation. The statistical analysis was performed with the SPSS 22.0 program. Results: 41 patients were collected, 28 men (68.3%) and 13 women (31.7%) with a mean age of 56.2 years (SD 17.6). The patients presented an average of 6.5 days of symptoms duration (SD 7), manifested as monoarthritis in 80.5% of the cases, with the knee being the most frequently affected joint (92.5%). In all patients, SF culture was negative. The most frequent diagnosis was microcrystalline arthritis in 21 patients (13 gout and 8 pseudogout), followed by the forms of onset of different chronic inflammatory arthropathies (9). Another 8 patients presented a mechanical joint effusion, in 1 patient the final diagnosis was not collected and there were 2 patients who presented other diagnoses (viral oligoarthritis, pigmented villonodular synovitis). Calprotectin values were higher in SF than in serum (mean 73, 058 vs 824.75 μg/g). A high positive correlation was found between the SC and the CRP (p<0.05, r=0.7) whereas the correlation with the number of leukocytes in SF (p<0.05, r=0.47) and with the ESR (<0.05, r=0.5) was moderate. The SFC was correlated with the CRP (p<0.05, r=0.45) and with the cell count in SF (p <0.05, r = 0.6), but not with the ESR. Regarding the different diagnoses, SC was numerically higher in microcrystalline arthritis (1157 μg/g) compared to non-microcrystalline arthritis (862 μg/g), although these differences were not significant due to the low number of patients in each group. Conclusion: Our preliminary results suggest that the analysis of SC could complement the information provided by a conventional analysis in the differential diagnosis of acute arthritis in situations in which an arthrocentesis is not possible. Studies with a greater number of patients and that include patients with septic arthritis are necessary. Disclosure of Interests: Marta Aguilar-Zamora: None declared, L Montolio-Chiva: None declared, Isabel de la Morena Speakers bureau: Abbvie, Celgene, Pfzier, UCB, Ghebro, Roche, Sanofi, Janssen., José María López Ortega: None declared, Carlos Feced Olmos: None declared, Ana V Orenes Vera: None declared, I Vázquez-Gómez: None declared, Elia Valls-Pascual: None declared, D Ybáñez-García: None declared, à Martínez-Ferrer: None declared, A Sendra-García: None declared, I Torner-Hernández: None declared, V Núñez-Monje: None declared, Juanjo J Alegre-Sancho: None declared